The relationship of training attitudes, perceived organisational support, psychological empowerment and organisational commitment among academic staff of Public Universities in Malaysia / Agatha Lamentan Muda - Muda, Agatha Lamentan (2019)
This study was an attempt that examined the level of, and relationship between the ThreeComponent-Model (TCM) of organisational commitment by Meyer and Allen that was the dependent variable of the study, and independent variables that comprised training attitudes, perceived organisational support and psychological empowerment. The selection of sample was conducted through a three-stage cluster random sampling method among the academic staff from three different faculties representing the cluster of Social Sciences and Humanities, Business and Management, and Science and Technology from three public comprehensive universities situated in Sabah, Sarawak and Peninsular Malaysia. A cross-sectional survey research questionnaire that was adapted from past studies was used as an instrument of data collection. All variables in the study that consists of organisational commitment, training attitudes, perceived organisational support and psychological empowerment met and exceeded the standard for the test of reliability using Cronbach’s coefficient alpha, the test of validity using factor analyses as well as the test of normality using histogram, box-plot, normal and detrended Q-Q plot, and skewness and kurtosis. The Statistical Package for the Social Sciences was used to analyse the data obtained from 225 respondents of the study. Descriptive statistic, T-test and ANOVA were used to analyse the level of organisational commitment, and Pearson’s correlation coefficient, simultaneous multiple regression analysis and moderated multiple regression were used to analyse the relationships between organisational commitment, training attitudes, perceived organisational support and psychological empowerment, and also with the demographic characteristics. The level of organisational commitment as experienced by respondents were found to be largely moderate but variations exist in terms of the level across the three different components of organisational commitment which comprised affective commitment, continuance commitment and normative commitment. As expected, the results of Pearson’s correlation indicated a significant and positive relationship between each of the above stated independent variables with the three components of organisational commitment as well as with the overall organisational commitment. The strongest relationship was between affective commitment and perceived organisational support, while simultaneous multiple regression analyses indicated that the two strongest predictors of organisational commitment as per the overall component were the self-determination dimension of psychological empowerment and the perceived organisational support. The multiple regression results indicated that 48.6 percent (R² = 0.486) of the variance in score of overall organisational commitment could be predicted by independent variables but none of the independent variable studied contributed to the variance in the continuance commitment score. Moreover that none of the relationship between overall organisational commitment with all three dimensions of training attitudes, perceived organisational support and overall psychological empowerment was moderated by the academic staffs age. This study provided evidence that there were significant relationships between effective training attitudes and practices, availability of intrinsic and extrinsic organisational support and excellent empowerment practices with organisational commitment among academic staff in the Malaysian public universities. All these lead to important implications towards related policies and administration.